Change of reception and lactate transport by cerebral endothelium under the influence of viral and bacterial inflammation in vitro - E. B. Boytsova; A. V. Morgun; E. D. Osipova; G. P. Martinova; A. B. Salmina (Фундаментальная и клиническая медицина, 2020)
Aim. To study the effect of neuroinflammation inducers of viral and bacterial origin on the reception and transport of lactate in endothelial cells of the brain in vitro.Materials and Methods. In the study, we incubated endothelial cells with bacterial inducers (lipopolysaccharide, E. coli) of various concentrations and inducer of viral inflammation (Poly I:C). After the exposure, we evaluated the proliferative activity of endothelial cells, change in transendothelial electrical resistance, and the concentration of extracellular lactate. We then performed an im-munocytochemistry investigation to record changes in the number of endothelial cells expressing the target molecules GPR81, MCT-1, IL-1β, TLR3 and ZO1.Conclusions. Disturbance of the transport and reception of lactate can contribute to the changes in structural and functional integrity of the blood-brain barrier caused by bacterial and viral inflammation.